Single-cell RNA sequencing reveals sex differences in the subcellular composition and associated gene-regulatory network activity of human carotid plaques - Sukhavasi, Katyayani; Mocci, Giuseppe; Ma, Lijiang; Hodonsky, Chani J.; Diez Benevante, Ernest; Muhl, Lars; Liu, Jianping; Gustafsson, Sonja; Buyandelger, Byambajav; Koplev, Simon; Lendahl, Urban; Vanlandewijck, Michael; et al. (Nature Cardiovascular Research, 2025)
Carotid stenosis causes ischemic stroke in both sexes, but the clinical presentation and plaque characteristics differ. Here we run deep single-cell sequencing of 7,690 human carotid plaque cells from male and female patients. While we found no sex differences in major cell types, we identified a predominance of the osteogenic phenotype in smooth muscle cells, immunomodulating macrophages (MPs) and endothelial cells (ECs) undergoing endothelial-to-mesenchymal transition in females. In males, we found smooth muscle cells with the chondrocytic phenotype, MPs involved in tissue remodeling and ECs with angiogenic activity. Sex-biased subcellular clusters were integrated with tissue-specific gene-regulatory networks (GRNs) from the Stockholm–Tartu Atherosclerosis Reverse Network Engineering Task study. We identified GRN195 involved in angiogenesis and T cell-mediated cytotoxicity in male ECs, while in females, we found GRN33 and GRN122 related to TREM2 − /TREM1 + MPs and endothelial-to-mesenchymal transition. The impact of GRN195 on EC proliferation in males was functionally validated, providing evidence for potential therapy targets for atherosclerosis that are sex specific. Using deep sequencing of human carotid plaque cells from male and female patients with carotid stenosis, Sukhavasi et al. identify sex-biased cell-type-specific gene-regulatory networks and different phenotypes in smooth muscle cells, including an osteogenic phenotype in females and a chondrocytic phenotype in males.